PRODUCTIVITY OF INDONESIAN AGRICULTURE: STUDY IN ASEAN - Utomo, Selamet Joko; Baskoro, Hanif Arif (EP FEB UNS, 2019)
Most ASEAN countries are categorized as an agrarian country where most of the population lives in agriculture. Agriculture in ASEAN is one of the mainstay sectors and has a direct role in national development. However, the condition of agricultural production in ASEAN is always fluctuating. This study aims to determine the level of agricultural productivity in ASEAN. Variables used in this study are agricultural value added, land area, labor and fertilizer consumption. Data analysis used in this research is Stochastic frontier analysis model (SFA) with logarithm model of linear frontier and trancedental logarithm of fixed effect and random effect to know production efficiency level. Consistently Malaysia and Vietnam are the countries that have the highest level of productivity than any other country from 2002-2014. In addition, based on the amount of sumbangsi, the area of land becomes the variable that gives the highest contribution of agricultural productivity in ASEAN.Keywords : Productivity, Agriculture, ASEAN